2nd Generation car security system - Khusbu, Nusrat Jahan; Nabila, Sarah Binte Nasir; Islam, Nushrat (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.